PENGARUH SISTEM MANAJEMEN MUTU ISO 9001:2008 TERHADAP PEMBELAJARAN BIOLOGI DI SMA NEGERI 2 BANGKO KABUPATEN ROKAN HILIR: The Effect of Quality Management System ISO 9001: 2008 on Biology Subject in SMA Negeri 2 Bangko Kabupaten Rokan Hilir - Ernamaiyanti Ernamaiyanti; Hayati Tatoe (UIR Press, 2017)
School education is expected to improve the quality of education. In improving the quality ofeducation, educational institutions use quality management system. Quality ManagementSystem (SMM) which has been implemented by SMA Negeri 2 Bangko, Rokan Hilir Regencyis SMM ISO 9001: 2008. The purpose of this study was to determine the effect of SMMISO 9001:2008 on Biology learning in SMA Negeri 2 Bangko, Rokan Hilir Regency. This typeof research includes field research field (field research) by using quantitative and qualitativeresearch. This research consists of: 1) dependent variable (Y): Biology learning 2)Independent variable (X): SMM ISO 9001: 2008. Data were analyzed using linearregression.There is an effect of variable quality management system ISO 9001: 2008 toBiology Learning. That is, the better the conditions of implementation of ISO 9001: 2008quality management system, then the Biology Learning will increase. Conversely the lowerthe implementation of ISO 9001: 2008 quality management system then Biology learning willalso decrease.